BELL1‐like homeobox genes regulate inflorescence architecture and meristem maintenance in rice. (5th March 2019) - Ikeda, Takuyuki; Tanaka, Wakana; Toriba, Taiyo; Suzuki, Chie; Maeno, Akiteru; Tsuda, Katsutoshi; Shiroishi, Toshihiko; Kurata, Tetsuya; Sakamoto, Tomoaki; Murai, Masayuki; Matsusaka, Hiroaki; Kumamaru, Toshihiro; et al.
Summary: Inflorescence architecture is diverse in angiosperms, and is mainly determined by the arrangement of the branches and flowers, known as phyllotaxy. In rice ( Oryza sativa ), the main inflorescence axis, called the rachis, generates primary branches in a spiral phyllotaxy, and flowers (spikelets) are formed on these branches. Here, we have studied a classical mutant, named verticillate rachis ( ri ), which produces branches in a partially whorled phyllotaxy. Gene isolation revealed that RI encodes a BELL1‐type homeodomain transcription factor, similar to Arabidopsis PENNYWISE/BELLRINGER/REPLUMLESS, and is expressed in the specific regions within the inflorescence and branch meristems where their descendant meristems would soon initiate. Genetic combination of an ri homozygote and a mutant allele of RI‐LIKE1 ( RIL1 ) (designated ri ril1/+ plant), a close paralog of RI, enhanced the ri inflorescence phenotype, including the abnormalities in branch phyllotaxy and rachis internode patterning. During early inflorescence development, the timing and arrangement of primary branch meristem (pBM) initiation were disturbed in both ri and ri ril1/+ plants. These findings suggest that RI and RIL1 were involved in regulating the phyllotactic pattern of the pBMs to form normal inflorescences. In addition, both RI and RIL1 seem to be involved in meristem maintenance, because the ri ril1 double‐mutant failed to establish or maintain the shoot apical meristem during embryogenesis. Significance Statement: We revealed that two BELL1‐like genes, RI and RIL1, play a crucial role in elaborating inflorescence architecture by regulating the timing and arrangement of primary branch meristem initiation. In addition, we suggest that these genes are also involved in meristem maintenance.